Social support strategies in adult patients with diabetes: a review of strategies in the USA and Europe. Issue 4 (July 2013) - Kirk, Julienne K; Ebert, Christine N; Gamble, Ginger P; Ebert, C Edward
Improvement of adherence in patients with a chronic disease state such as diabetes can be facilitated through well-crafted social support strategies. Family and friends are support options for many individuals living with diabetes. A systematic search of three databases was conducted to evaluate literature published from 2006 to April 2013 regarding social support in adults with diabetes conducted in the USA and Europe. While various studies had different findings, the overall trend shows that social support can result in a positive influence on both the ability of the patient to initiate and sustain diabetes management that can potentially result in positive health outcomes. This appears true even when the patient has low psychosocial skills and a small social support network. Healthcare professional involvement also correlates with patient improvement in specific outcomes not overlapped by the patient's social network. Support facilitated by peers can be a viable option along with the multitude of electronic options to help with social support.